Evaluasi Kinerja Metoda Analisis Pengukuran Neutron (APN) - Arifin, Zaenal; Sasongko, Dwi P; Munir, M (BERKALA FISIKA, 2010)
Evaluation of Neutron Activation Analysis (NAA) methods performance has been done. The objective is to validate the data form these analysis on the determination of the trace element concentration in the waters and sediments. This evaluation covering test of devices stability, background counting, Figure of Merit (FOM), Critical Level (Lc), Detection Limit (LD), Determination Limit (LQ) and test of quality result. Result show that device in stabil conditionÂ  have background counting about 0.0037 to 0.1806 cps, Figure of Merit (FOM) about to 0.0045 to 0.1732 secon. The data result analysis above Critical Level (LC), in LC about 0.07 to 16.42 ppb. Detection Limit (LD) about 0.14 to 32.93 ppb in significant 95% expect Hg obtained LD 1.26 ppb. Determination Limit (LQ) about 0.44 to 100.10 ppb. Test of quality result show that of standardized difference about 15.17% to above 50% and Precision result analysis about 0.01% to 99.00%. Â  Keywords : NAA Methods, Trace element, devices stability, background counting, Figure of Merit (FOM), Critical Level (Lc), Detection Limit (LD), Determination Limit (LQ) and test of quality result.